Quantifying adoption rates and energy savings over time for advanced energy-efficient manufacturing technologies. (20th September 2019) - Hanes, Rebecca; Carpenter, Alberta; Riddle, Matthew; Graziano, Diane J.; Cresko, Joe
Abstract: Energy-efficient manufacturing technologies can reduce energy consumption and lower operating costs for manufacturing facilities, but up-front costs and increased process complexity frequently lead to manufacturers being reluctant to adopt such technologies. To avoid over-estimating the benefits of advanced energy-efficient manufacturing technologies, it is necessary to account for how quickly and how widely the technology will be adopted by manufacturers. This work develops a method for estimating manufacturing technology adoption rates using quantitative technology characteristics including energetic, economic, and technical criteria that capture both incentives (such as energy and cost savings) and disincentives (such as increased process complexity) for technology adoption. This method is unique in that it can be applied before or after a technology reaches the market; other adoption rate estimation methods require sales data and can only be applied post-market. Eleven technology characteristics are considered, with each characteristic weighted to reflect its impact on the overall technology adoption rate. Technology characteristic data is used to estimate model parameters for the Bass diffusion curve, which quantifies the change in the number of new technology adopters in a population over time. Finally, energy savings at the sector level are calculated over time by multiplying the number of new technology adopters at each time step with the technology's facility-level energy savings. The proposed method is demonstrated with an application to glass industry manufacturing technologies using technology data obtained from the U.S. Department of Energy's 2017 bandwidth study. The potential energy savings for each technology and the rate at which each technology is adopted in the sector are quantified and used to identify the technologies which offer the greatest cumulative sector-level energy savings over a period of 20 years. Highlights: A method for incorporating adoption rates into prospective manufacturing technology analyses is developed. The method is demonstrated with an application in the U.S. glass industry. Insights from and benefits of the proposed method are discussed.